RANCANG BANGUN MESIN GERGAJI BESI SEMI OTOMATIS: MANUFACTURING SEMI AUTOMATIC HAKSAW - Nurisna, Zuhri (Jurnal Teknik Mesin, 2023)
Hacksaw is a saw that is used to cut metal objects such as iron. Hacksaws are still widely used for metal cutting processes because they have the advantage of not generating excessive heat during the cutting process which can affect the metal structure. Behind these advantages, cutting metal using a hacksaw manually is less efficient in time and the cutting results are less neat. The solution to this problem is to make a hacksaw with an electric motor drive. The design of this automatic hacksaw machine uses a drive in the form of an electric motor with a capacity of 0.5 HP. The output from the rotation of the electric motor is forwarded using pulleys and gears with a ratio of 12:1, and is continued using a slider to move the hacksaw blade back and forth. Reduction of rotation is intended to increase the cutting torque. The design of this hacksaw machine also adds a feature in the form of an automatic switch to stop the movement when the cut is complete. Based on the test results of the automatic hacksaw machine used for cutting carbon steel, the cutting capacity is 2.4 cm2/minute and the electric motor power calculation has a power capacity of 2.5 W/cm2. The results of cutting the material are also straight and neat without causing heat during the material cutting process.